2
$\begingroup$

I am having quite a bit of trouble trying to find a closed form (or a really fast way to compute) for the infinite sum $$\sum_{n=1}^{\infty} a^n \dfrac{\gamma(n+1,b)}{\Gamma(n+1)\Gamma(n)}$$ where $\gamma(n,b) = \int_0^bz^{n-1}e^{-z} dz$ is the lower incomplete Gamma function and $a,b > 0$.

Any ideas how to solve this?

$\endgroup$
1
$\begingroup$

Since: $$\sum_{n\geq 1}\frac{z^{n-1}}{\Gamma(n)\Gamma(n+1)}=\frac{I_1(2\sqrt{z})}{\sqrt{z}}$$ provided that $a,b\in\mathbb{R}^+$ you series equals: $$ a \int_{0}^{b}\frac{I_1(2\sqrt{az})}{\sqrt{az}}e^{-z}\,dz = \int_{0}^{ab}\frac{I_1(2\sqrt{z})}{\sqrt{z}}e^{-z/a}=2\int_{0}^{\sqrt{ab}}I_1(2u)\,e^{-u^2/a}\,du.$$

$\endgroup$
  • $\begingroup$ What is $I_1(z)$? $\endgroup$ – robjohn Apr 2 '15 at 11:19
  • $\begingroup$ @robjohn: the modified Bessel function of the first kind. $\endgroup$ – Jack D'Aurizio Apr 2 '15 at 11:22
  • $\begingroup$ @JackD'Aurizio: (+1) heh, I just figured that out while identifying the same function in this answer. $\endgroup$ – robjohn Apr 2 '15 at 12:07
  • $\begingroup$ Why the downvote? $\endgroup$ – Jack D'Aurizio Apr 22 '15 at 20:22
  • $\begingroup$ @Jack D'Aurizio Converting series back to the integral form is not the expected way of simplification. $\endgroup$ – Harry Peter Apr 24 '15 at 13:05
-1
$\begingroup$

$\sum\limits_{n=1}^\infty\dfrac{a^n\gamma(n+1,b)}{\Gamma(n+1)\Gamma(n)}$

$=\sum\limits_{n=0}^\infty\dfrac{a^{n+1}\gamma(n+2,b)}{\Gamma(n+2)\Gamma(n+1)}$

$=\sum\limits_{n=0}^\infty\dfrac{a^{n+1}\int_0^bz^{n+1}e^{-z}~dz}{n!(n+1)!}$

$=\left[-\sum\limits_{n=0}^\infty\sum\limits_{k=0}^{n+1}\dfrac{a^{n+1}z^ke^{-z}}{n!k!}\right]_0^b$ (according to http://en.wikipedia.org/wiki/List_of_integrals_of_exponential_functions)

$=\sum\limits_{n=0}^\infty\dfrac{a^{n+1}}{n!}-\sum\limits_{n=0}^\infty\sum\limits_{k=0}^{n+1}\dfrac{a^{n+1}b^ke^{-b}}{n!k!}$

$=ae^a-\sum\limits_{n=0}^\infty\dfrac{a^{n+1}b^{n+1}e^{-b}}{n!(n+1)!}-\sum\limits_{n=0}^\infty\sum\limits_{k=0}^n\dfrac{a^{n+1}b^ke^{-b}}{n!k!}$

$=ae^a-abe^{-b}{_0F_1}(;2;ab)-\sum\limits_{k=0}^\infty\sum\limits_{n=k}^\infty\dfrac{a^{n+1}b^ke^{-b}}{n!k!}$

$=ae^a-abe^{-b}{_0F_1}(;2;ab)-\sum\limits_{k=0}^\infty\sum\limits_{n=0}^\infty\dfrac{a^{n+k+1}b^ke^{-b}}{(n+k)!k!}$

$=ae^a-abe^{-b}{_0F_1}(;2;ab)-ae^{-b}\Phi_3(1,1;a,ab)$ (according to http://en.wikipedia.org/wiki/Humbert_series)

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.